A Novel Approach to the Detection and Characterization of PAH Cations and PAH-Photoproducts. Issue Volume 9:Issue S297(2013) (21st February 2014) - Kokkin, D. L.; Simon, A.; Marshall, C.; Bonnamy, A.; Joblin, C.
Abstract: Cationic polycyclic aromatic hydrocarbons (PAHs) are attractive candidates for the Diffuse Interstellar Bands, but to date not a single PAH species has been identified on the basis of a spectral agreement. This indicates either that the molecular diversity is very large or that the candidates that have been considered are not the correct ones. In particular, small/medium-sized PAH cations are submitted to photodissociation under UV photons from stars. Therefore it is of interest to characterize the spectroscopic properties of key breakdown products. Furthermore, these studies should be performed under conditions that mimic those found in interstellar space, which leads to additional experimental difficulties. We describe the approach we are developing with the PIRENEA set-up and present results on the 1-Methylpyrene cation and photo-derived species. Experimental measurements are guided by calculations based on density functional theory.